2011
DOI: 10.1109/tnano.2010.2091422
|View full text |Cite
|
Sign up to set email alerts
|

Surface Effects on the Jump-in Instability of Nanomechanical Structures

Abstract: Surface effects are indispensable for crystalline materials when the characteristic size falls into nanoscale. In this paper, the size-dependent jump-in instability of an ultrathin film, omnipresent in nanoelectromechanical systems, is analyzed by incorporating the effects of surface energies. Based on a nonclassical thin plate theory including surface effects and the thermodynamic energy balance theorem, the jump-in instability mechanism of the film is established to determine the critical separation gap and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
(42 reference statements)
0
3
0
Order By: Relevance
“…The importance of surface stress effects was illustrated by employing the energy minimization method within the framework of continuum mechanics. The finding of Lü et al [93] on the occurrence of jump-in instability in a nanoplate suggests that surface elasticity can affect the critical separation gap but not the contact length between the ultrathin Brought to you by | Western University Authenticated Download Date | 6/8/15 3:42 PM film and substrate. Another of their publications reported that the surface effect will become more significant and indispensable when the thickness of functionally graded films reduces to the intrinsic length scale [94].…”
Section: Surface Elasticity Theory On Complex Nanostructures and Nanomentioning
confidence: 97%
“…The importance of surface stress effects was illustrated by employing the energy minimization method within the framework of continuum mechanics. The finding of Lü et al [93] on the occurrence of jump-in instability in a nanoplate suggests that surface elasticity can affect the critical separation gap but not the contact length between the ultrathin Brought to you by | Western University Authenticated Download Date | 6/8/15 3:42 PM film and substrate. Another of their publications reported that the surface effect will become more significant and indispensable when the thickness of functionally graded films reduces to the intrinsic length scale [94].…”
Section: Surface Elasticity Theory On Complex Nanostructures and Nanomentioning
confidence: 97%
“…When undergoing a large deformation (A > A c ) during the systole of the heart, the MEH device will contact with the surrounding tissues at the centre part. Here, the adhesion effect between the MEH device and the surrounding tissues is neglected, then the contact length will be zero [32,33], that is, the device will have only the centre point contacting with the surround tissues. For simplicity, the deformation of the surrounding tissues is further ignored or the surrounding tissues are assumed rigid when compared with the MEH device, then the displacement and the slope at the device centre will keep at w| x=0 = A c and w | x=0 = 0.…”
Section: (A) Free Deformation (A < a C )mentioning
confidence: 99%
“…When undergoing a large deformation (A > A c ) during the systole of the heart, the MEH device will contact with the surrounding tissues at the centre part. Here, the adhesion effect between the MEH device and the surrounding tissues is neglected, then the contact length will be zero [32,33], that is, the device will have only the centre point contacting with the surround tissues.…”
Section: (A) Free Deformation (A < a C )mentioning
confidence: 99%